Safety Assessment of Concrete Gravity Dams: Hydromechanical Coupling and Fracture Propagation - Maria Luísa Braga Farinha; Nuno Monteiro Azevedo; Sérgio Oliveira (Geosciences)
For the safety assessment of concrete dam–foundation systems, this study used an explicit time-stepping small-displacement algorithm, which simulates the hydromechanical interaction and considers the discrete representation of the foundation discontinuities. The proposed innovative methodology allows for the definition of more reliable safety factors and the identification of more realistic failure modes by integrating (i) softening-based constitutive laws that are closer to the real behavior identified experimentally in concrete–concrete and concrete–rock interfaces; (ii) a water height increase that can be considered in both hydraulic and mechanical models; and (iii) fracture propagation along the dam–foundation interface. Parametric studies were conducted to assess the impact of the mechanical properties on the global safety factors of three gravity dams with different heights. The results obtained using a coupled/fracture propagation model were compared with those from the strength reduction method and the overtopping scenario not considering the hydraulic pressure increase. The results show that the safety assessment should be conducted using the proposed methodology. It is shown that the concrete–rock interface should preferably have a high value of fracture energy or, ideally, higher tensile and cohesion strengths and high associated fracture energy. The results also indicate that with a brittle concrete–rock model, the predicted safety factors are always conservative when compared with those that consider the fracture energy.